From southern swamps to cosmopolitan model: Humanity's unfinished history with mosquitofish. Issue 1 (1st September 2021) - Fryxell, David C.; Moffett, Emma R.; Kinnison, Michael T.; Simon, Kevin S.; Palkovacs, Eric P.
Abstract: The most widespread and numerous inland fish in the world is likely the mosquitofish ( Gambusia affinis and G. holbrooki, Poeciliidae). Much has been written about the basic biology, the current distribution and the negative impacts of non‐native populations of mosquitofish. Here, we instead review the relationship of humanity with mosquitofish. First, we review the early literature on the species and aim to resolve its path towards becoming the globally dominant fish for biological control of mosquitoes. We identify the initial advocates of mosquitofish use, we examine the reasons behind their advocacy, and we document the spread of their viewpoints into and from the globally foundational mosquito control texts. Second, we identify the people and institutions that facilitated early international translocations of mosquitofish, including, among others, David Starr Jordan, the Rockefeller Foundation and the International Red Cross. Third, we discuss the reduction in mosquitofish translocation and use during and after WWII, initially stemming from the discovery and use of other methods, like DDT and later from a recognition of the negative ecological consequences of non‐native mosquitofish populations. Fourth, we propose that the future utility of mosquitofish is largely in its value as a model study organism. We provide an overview of the contributions mosquitofish have made to some major fields in biology. Finally, we suggest that the value of mosquitofish as a model system should increase into the future, behind a momentum of research advances, and as human‐mediated range expansion will permit access to mosquitofish by yet greater numbers of biologists worldwide.